Critical Discourse Analysis: The Meaning of #Indonesiagelap on the X Platform - Bintang Timur; Siti Khumayah; Aghnia Dian Lestari (Jurnal Bisnis dan Komunikasi Digital, 2026)
The emergence of the social media platform X has also transformed the way people understand and interpret the social reality around them. Through the use of hashtags on X, individuals not only share information but also convey their experiences and perspectives. Hashtags have become a vital tool for bringing people together and sparking discussions on specific topics. The hashtag #Indonesiagelap emerged as a protest against public dissatisfaction with the government, which is perceived as leading Indonesia’s future into “darkness” due to a series of controversial government policies and a deteriorating national economy. This study aims to conduct a Critical Discourse Analysis of the hashtag #Indonesiagelap to examine the meanings it conveys to other users on the X platform. This study employs a qualitative approach using the phenomenological method. Data collection techniques include observation, in-depth interviews with three informants who engage with the #Indonesiagelap hashtag, and supporting documentation. Data analysis is conducted descriptively through the processes of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the hashtag #Indonesiagelap is interpreted by X users as a symbol of collective criticism and disappointment regarding the prevailing socio-political conditions. Based on textual practices, discourse, and the underlying social context, this hashtag serves not merely as an indicator of an issue but also as a communication tool capable of fostering a shared understanding of meaning and cultivating critical awareness among X users